Semidiurnal internal tide energy fluxes and their variability in a Global Ocean Model and moored observations. Issue 3 (10th March 2017) - Ansong, Joseph K.; Arbic, Brian K.; Alford, Matthew H.; Buijsman, Maarten C.; Shriver, Jay F.; Zhao, Zhongxiang; Richman, James G.; Simmons, Harper L.; Timko, Patrick G.; Wallcraft, Alan J.; Zamudio, Luis
Abstract: We examine the temporal means and variability of the semidiurnal internal tide energy fluxes in 1/25° global simulations of the Hybrid Coordinate Ocean Model (HYCOM) and in a global archive of 79 historical moorings. Low‐frequency flows, a major cause of internal tide variability, have comparable kinetic energies at the mooring sites in model and observations. The computed root‐mean‐square (RMS) variability of the energy flux is large in both model and observations and correlates positively with the time‐averaged flux magnitude. Outside of strong generation regions, the normalized RMS variability (the RMS variability divided by the mean) is nearly independent of the flux magnitudes in the model, and of order 23% or more in both the model and observations. The spatially averaged flux magnitudes in observations and the simulation agree to within a factor of about 1.4 and 2.4 for vertical mode‐1 and mode‐2, respectively. The difference in energy flux computed from the full‐depth model output versus model output subsampled at mooring instrument depths is small. The global historical archive is supplemented with six high‐vertical resolution moorings from the Internal Waves Across the Pacific (IWAP) experiment. The model fluxes agree more closely with the high‐resolution IWAP fluxes than with the historical mooring fluxes. The high variability in internal tide energy fluxes implies that internal tide fluxes computed from short observational records should be regarded as realizations of a highly variable field, not as "means" that are indicative of conditions at the measurement sites over all time. Key Points: The RMS variability in internal tide energy flux is large in both model and observations Mode‐1 internal tide fluxes compare much better with observations HYCOM compares very well with internal tides fluxes from the IWAP experiment